Water is life, guard it well - Abd Razak, Dzulkifli (2008)
HANOI, judging by the traffic, especially the millions of motorbikes that clog the streets, is a city in a hurry. So, too, the number of construction projects being undertaken. Of particular significance is the new Phu Quoc International Airport which had its groundbreaking ceremony last week. Scheduled to be completed in mid2012, it will a breakthrough not only for Phu Quoc Island, referred to as the "untapped pearl" (watch out Penang!) but also for the country. Already, most apparent is the rate at which businesses are being conducted just about anywhere, even on fivefoot ways and public spaces.